Microplastics and environmental pollutants: Key interaction and toxicology in aquatic and soil environments - Xiang, Yujia; Jiang, Li; Zhou, Yaoyu; Luo, Zirui; Zhi, Dan; Yang, Jian; Lam, Su Shiung (Journal of hazardous materials, 2022)
Nowadays, a growing number of microplastics are released into the environment due to the extensive use and inappropriate management of plastic products. With the increasing body of evidence about the pollution and hazards of microplastics, microplastics have drawn major attention from governments and the scientific community. As a kind of emerging and persistent environmental pollutants, microplastics have recently been detected on a variety of substrates in the world. Therefore, this paper reviews the recent progress in identifying the sources of microplastics in soil, water, and atmosphere and describing the transport and fate of microplastics in the terrestrial, aquatic and atmospheric ecosystems for revealing the circulation of microplastics in the ecosystem. In addition, considering the persistence of microplastics, this study elucidates the interactions of microplastics with other pollutants in the environment (i.e., organic pollutants, heavy metals) with emphasis on toxicity and accumulation, providing a novel insight into the ecological risks of microplastics in the environment. The negative impacts of microplastics on organisms and environmental health are also reviewed to reveal the environmental hazards of microplastics. The knowledge gaps and key research priorities of microplastics are identified to better understand and mitigate the environmental risks of microplastics. [Display omitted] •Source, transport and fate of microplastics are comprehensively reviewed.•Interaction between microplastics and other environmental pollutants is discussed.•Environmental risks and negative impacts of microplastics are discussed.•Knowledge gaps and research priorities of microplastics are presented.